2021
DOI: 10.3390/microorganisms9122473
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of 22 Antibiotics against Achromobacter Isolates from People with Cystic Fibrosis. Are There New Therapeutic Options?

Abstract: Bacteria belonging to the genus Achromobacter are increasingly isolated from respiratory samples of people with cystic fibrosis (PWCF). The management of this multidrug-resistant genus is challenging and characterised by a lack of international recommendations, therapeutic guidelines and data concerning antibiotic susceptibility, especially concerning the newer antibiotics. The objective of this study was to describe the antibiotic susceptibility of Achromobacter isolates from PWCF, including susceptibility to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…As described in an article by Isler et al, A. xylosoxidans is intrinsically resistant to penicillins, first-and second-generation cephalosporins, ceftriaxone, cefotaxime, aztreonam, tetracycline, and aminoglycosides. 4 In our study, Aztreonam and ceftriaxone were zero percent (0%) susceptible to Achromobacter. Whereas, aminoglycosides such as Amikacin and Gentamicin had shown a very low sensitivity pattern in vitro with 9% and 5% sensitivity, respectively.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…As described in an article by Isler et al, A. xylosoxidans is intrinsically resistant to penicillins, first-and second-generation cephalosporins, ceftriaxone, cefotaxime, aztreonam, tetracycline, and aminoglycosides. 4 In our study, Aztreonam and ceftriaxone were zero percent (0%) susceptible to Achromobacter. Whereas, aminoglycosides such as Amikacin and Gentamicin had shown a very low sensitivity pattern in vitro with 9% and 5% sensitivity, respectively.…”
Section: Discussionmentioning
confidence: 45%
“…These results were similar to the study by Beaurelle et al which also has reported the zero (0%) susceptibility to Aztreonam and Gentamicin, and only 13% sensitivity for Amikacin. 4 The most effective agents against Achromobacter species are Trimethoprimsulfamethoxazole, ceftazidime, piperacillin and carbapenems. 31 In our study, the maximum susceptibility is seen for Cotrimoxazole (80.59%), followed by carbapenems like Meropenem (80.52%) and Imipenem with 68.83%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…no guidelines or previous reports have been published, and antibiotic stewardship has been crucial to act on both pathogens and thus reduce adverse events. However, for A. xylosoxidans , there are no solid data, in vivo or in vitro, regarding optimal topical antibiotic treatment [15]. Following the antibiogram and after a review of the literature, we decided to treat the patients with topical ozenoxacin 1% cream for 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…It has also shown in vitro activity against clinical isolates of Achromobacter spp. from patients with CF ( 15 ) and of B. pseudomallei from patients with mainly blood, lung, skin, and soft tissue infections ( 8 ).…”
Section: Introductionmentioning
confidence: 99%